2022
DOI: 10.2147/ott.s329095
|View full text |Cite
|
Sign up to set email alerts
|

Amivantamab in the Treatment of Metastatic NSCLC: Patient Selection and Special Considerations

Abstract: Amivantamab is a bispecific antibody that recognizes epidermal growth factor receptor (EGFR) and MET proto-oncogene (MET). In May 2021, the Food and Drug Administration gave an accelerated approval of amivantamab for the treatment of non-small cell lung cancer (NSCLC) patients with EGFR exon 20 insertions (Exon20ins) who progressed after platinum-based chemotherapy. Amivantamab prevents ligand binding to EGFR and MET and the dimerization of the receptors suppressing the downstream signal transduction. Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
0
7
0
1
Order By: Relevance
“…Considering the results, innovative treatments under development for the post-osimertinib and Pt-doublet setting, such as amivantamab, EGFR–mesenchymal epithelial transition factor bispecific antibody, and treatment combined with lazertinib (a third-generation EGFR-TKI) [ 31 ] and patritumab deruxtecan (human EGFR 3-directed monoclonal antibody–drug conjugate) [ 32 ], may be able to provide better treatment choices in this line of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the results, innovative treatments under development for the post-osimertinib and Pt-doublet setting, such as amivantamab, EGFR–mesenchymal epithelial transition factor bispecific antibody, and treatment combined with lazertinib (a third-generation EGFR-TKI) [ 31 ] and patritumab deruxtecan (human EGFR 3-directed monoclonal antibody–drug conjugate) [ 32 ], may be able to provide better treatment choices in this line of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A recent ASCO (2022) study demonstrated that mobocertinib and amivantamab had similar efficacy in NSCLC patients with EGFR ex20ins who had disease progression during or after platinum-based chemotherapy. In the first-line study, PAPILLON (NCT04538664) ( 89 ), an international, multicenter, randomized, open-label, Phase III clinical trial, 308 patients were randomized (153 to amivantamab -chemotherapy and 155 to chemotherapy alone). The findings indicated that the amivantamab chemotherapy group achieved a significantly longer PFS than the chemotherapy group (median 11.4 vs. 6.7 months; hazard ratio for disease progression or death 0.40).…”
Section: New Therapeutic Strategies For Patients With Nsclc Who Have ...mentioning
confidence: 99%
“…The CHRYSALIS trial demonstrated that amivantamab was effective in reducing tumor size and improving survival in patients with lung cancer with EGFR Ex20Ins mutation [ 7 ]. Table 1 shows the anti-EGFR antibodies approved for the treatment of lung cancer between 2004 and 2021, where it is demonstrated for different reasons that amivantamab is the best treatment option [ 8 ].…”
Section: Reviewmentioning
confidence: 99%